2018
DOI: 10.1038/s41598-018-23341-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hedgehog signaling suppresses proliferation and microcyst formation of human Autosomal Dominant Polycystic Kidney Disease cells

Abstract: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is caused by mutation of PKD1 or PKD2, which encode polycystin 1 and 2, respectively. The polycystins localize to primary cilia and the functional loss of the polycystin complex leads to the formation and progressive growth of fluid-filled cysts in the kidney. The pathogenesis of ADPKD is complex and molecular mechanisms connecting ciliary dysfunction to renal cystogenesis are unclear. Primary cilia mediate Hedgehog signaling, which modulates cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…We also identified the ciliary protein ARL13b. This protein is involved in hedgehog signaling [27,28], which in turn appears to be involved in cystogenesis [29] and even malignancy [30].…”
Section: Discussionmentioning
confidence: 99%
“…We also identified the ciliary protein ARL13b. This protein is involved in hedgehog signaling [27,28], which in turn appears to be involved in cystogenesis [29] and even malignancy [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse embryo, deletion of Tulp3 causes upregulation of the Sonic Hedgehog (Shh) pathway in the neural tube in a Gli-dependent manner and causes skeletal defects consistent with Shh pathway dysregulation [19][20][21][22]. In addition, it has been postulated that activation of the Shh pathway is associated with ADPKD [10,36]. However, Tulp3…”
Section: Regulation Of a Cilia-dependent Cyst Activation Pathway By Tmentioning
confidence: 99%
“…Accordingly, Song et al [9] reported an upregulation of some HH signalling components (i.e., PTCH1 and GLI2 mRNAs) in renal cysts from patients with PKD1, suggesting a modest role of the pathway in human cystogenesis. In a very recent work, Silva et al [33] elegantly show that although the transcription factor GLI1 increased in ADPKD primary renal epithelial cells compared to normal renal cells, no altered activation of the HH pathway in the cilia were found. Likewise, in vitro studies showed no difference between both types of cells in proliferation and microcyst development, even after treatment with cyclic AMP [33].…”
Section: Discussionmentioning
confidence: 98%
“…In a very recent work, Silva et al [33] elegantly show that although the transcription factor GLI1 increased in ADPKD primary renal epithelial cells compared to normal renal cells, no altered activation of the HH pathway in the cilia were found. Likewise, in vitro studies showed no difference between both types of cells in proliferation and microcyst development, even after treatment with cyclic AMP [33].…”
Section: Discussionmentioning
confidence: 98%